Plasma grafting of polypropylene with organosilanes and its alkylamine treatment. (May 2016) - Prachar, Jozef; Novak, Igor; Kleinova, Angela; Gemeiner, Pavol; Omastova, Maria; Chmela, Stefan; Borsig, Eberhard
Abstract: This work focuses on the direct grafting of polypropylene (PP) with tetraethoxysilane (TEOS) in the high energy plasma conditions to obtain hydrophilic surface even after its multiple washing by organic solvents. The plasma polymerisation of TEOS led to the introduction of the silicon-containing functional groups on the PP surface. However, using this method, two kinds of materials on the TEOS-grafted PP surface were obtained: the fixed organosilanes and a mixture of unbound organosilanes, which were extractable from the surface using the organic solvents (methanol, chloroform). These unbound organosilanes were used for their subsequent binding onto the unwashed TEOS-grafted PP using propylamine. This treatment improved the permanent hydrophilicity of grafted surface even after its multiple washing in comparison with washed TEOS-grafted and plasma-treated PP. For characterization of modified surfaces, Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Photo-electron Spectroscopy (XPS) were used. The surface roughness and hydrophilicity were measured using Atomic Force Microscopy (AFM) and static Water Contact Angle (WCA) measurement. Highlights: New approach of the direct plasma grafting of PP with TEOS and its propylamine treatment. Increase in content of the silicon-containing functional groups on the PP surface using the plasma grafting. Improve of permanent hydrophilicity of the TEOS-grafted PP using its propylamine treatment.